PENGARUH PENDEKATAN LEARNING TRAJECTORY TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV UPT SD INPRES KARUNRUNG KOTA MAKASSAR - Ita; Rahmawati Patta; Syamsuryani Eka Putri Atjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1). determine the application of the Learning Trajectory approach in elementary schools, (2). determine the description of elementary school students' understanding of mathematical concepts, and (3). the effect of the Learning Trajectory approach on elementary school students' understanding of mathematical concepts. This study is included in experimental research with a quantitative approach. The research design used in this study is Quasi Experiment with a nonequivalent control group design type. The population in this study were all fourth grade students of UPT SD Inpres Karunrung, Makassar City. The sample in this study was 40 students selected through purposive sampling techniques. The data collection techniques used were observation of implementation by teachers, students, and concept understanding tests. Data analysis used descriptive and inferential analysis. The results of the descriptive analysis showed that the percentage of implementation of the learning process using the learning trajectory approach on teachers was in the good category at the first meeting and the second meeting with a very good category. The results of the inferential analysis using the independent sample t-test showed a difference in posttest results between the experimental class and the control class. This indicates a difference in students' understanding of mathematical concepts after being given treatment. So it can be concluded that: (1) the learning process using the learning trajectory approach went well, (2) the results of the student tests showed differences in students' understanding of mathematical concepts in learning, (3) there was a significant influence on the application of the learning trajectory approach on the understanding of mathematical concepts of class IV students at UPT SD Inpres Karunrung, Makassar City.